2006
DOI: 10.1016/j.virol.2006.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of small molecule inhibitors of HIV-1 entry with CCR5

Abstract: The CC-chemokine receptor 5 (CCR5) is the major coreceptor for macrophage-tropic (R5) HIV-1 strains. Several small molecule inhibitors of CCR5 that block chemokine binding and HIV-1 entry are being evaluated as drug candidates. Here we define how CCR5 antagonists TAK-779, AD101 (SCH-350581) and SCH-C (SCH-351125), which inhibit HIV-1 entry, interact with CCR5. Using a mutagenesis approach in combination with a viral entry assay to provide a direct functional read out, we tested predictions based on a homology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
107
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 75 publications
10
107
1
1
Order By: Relevance
“…Note that an Ile-Met change at position 189 in TM5 indirectly compromises the antiviral activity of a different CCR5 inhibitor, SCH-C, again without this residue being part of the inhibitor-binding site (48). Another probable long-range effect on the CCR5 structure involves the T82A substitution, which partially impairs the inhibitory activity of TAK779 but not that of other small molecules, including AD101 and SCH-C (7,27). Overall, the two changes at residue 82 that create the CCR5-T82K and CCR5-T82P CAMs have different effects on VVC and MVC binding and HIV-1 entry, presumably because they alter the overall geometry of CCR5 in different ways that are not yet understood at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Note that an Ile-Met change at position 189 in TM5 indirectly compromises the antiviral activity of a different CCR5 inhibitor, SCH-C, again without this residue being part of the inhibitor-binding site (48). Another probable long-range effect on the CCR5 structure involves the T82A substitution, which partially impairs the inhibitory activity of TAK779 but not that of other small molecules, including AD101 and SCH-C (7,27). Overall, the two changes at residue 82 that create the CCR5-T82K and CCR5-T82P CAMs have different effects on VVC and MVC binding and HIV-1 entry, presumably because they alter the overall geometry of CCR5 in different ways that are not yet understood at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…This resistance pathway often, but not always, results in a virus that is resistant to multiple CCR5 antagonists (22,33,39,53,56). The CCR5 antagonists that have been used clinically all seem to bind to a hydrophobic region in the transmembrane helices of CCR5 and induce conformational alterations in the extracellular domains of the coreceptor that inhibit recognition by gp120 (13,31,32,46,52). These conformational alterations are similar though not identical as judged by the ability of these compounds to affect the binding of various conformation-dependent monoclonal antibodies to CCR5.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between gp120 and CCR5 occur in at least two distinct areas: (i) the bridging sheet and the stem of the V3 loop interact with sulfated tyrosine residues in the NЈ terminus of CCR5, and (ii) the crown of the V3 loop is thought to engage the extracellular loops (ECLs), particularly ECL2, of CCR5 (10-12, 14, 18, 28). Small-molecule CCR5 antagonists bind to a hydrophobic pocket in the transmembrane helices of CCR5 and exert their effects on HIV by altering the position of the ECLs, making them allosteric inhibitors of HIV infection (13,31,32,46,52). The conformational changes in CCR5 that are induced by CCR5 antagonists vary to some degree with different drugs, as evidenced by differential binding of antibodies and chemokines to various drug-bound forms of CCR5 (47,54).…”
mentioning
confidence: 99%
“…The small-molecule CCR5 antagonists sit in the pocket formed by the transmembrane (TM) domains of CCR5 (Dragic et al, 2000;Tsamis et al, 2003;Nishikawa et al, 2005;Maeda et al, 2006;Seibert et al, 2006), whereas HIV gp120 binds to the outer surface of CCR5, mainly by making contact with the N terminus and the second extracellular loop (ECL) of CCR5 (Rucker et al, 1996;Doranz et al, 1997;Dragic et al, 1998;Farzan et al, 1998;Rabut et al, 1998;Ross et al, 1998;Blanpain et al, 1999;Howard et al, 1999;Dragic, 2001). Alanine scanning mutagenesis studies of CCR5 revealed that several key residues required for the small molecule CCR5 antagonists to block HIV entry are located in the TM domains (Dragic et al, 2000;Tsamis et al, 2003;Nishikawa et al, 2005;Maeda et al, 2006;Seibert et al, 2006). These residues were identified by studying one or two classes of CCR5 antagonists.…”
mentioning
confidence: 99%